Penelitian PERAN SUAMI PADA PELAKSANAAN PAP SMEAR DALAM UPAYA DETEKSI DINI CA CERVIX - Ariani Sulistyorini; Enur Nurhayati Muchsin; Dwi Novikahwati (STIKES dan AKZI Karya Husada Kediri, 2022)
The Husbands play an important role in maintaining family health, one of which is by maintaining the wife's reproductive health, by playing a role and supporting the implementation of Pap smears for early detection of cervical cancer, can reduce the number of patients with cervical cancer. In general, women of childbearing age do not want to carry out a pap smear examination because of the lack of support from their husbands and lack of knowledge about pap smears. The purpose of the study was to determine the husband's role in the implementation of the Pap smear in an effort to detect cervical cancer early. The research design used a descriptive design with a population of 133 respondents, a large sample of 33 respondents, using a purposive sampling technique, the single variable is the husband's role in the implementation of Pap Smear in Cervix Ca Prevention Efforts. This research was conducted on 28 February – 26 March 2022, the research instrument was a questionnaire. Analysis of the data using the percentage formula and interpreted quantitatively. The results showed that from 33 respondents most of the respondents had a sufficient role as many as 24 respondents (73%) and almost half of the respondents had a good role as many as 9 respondents (27%). The husband's role in the pap smear implementation is influenced by several factors, namely education, income and experience in getting information about pap smears. Respondents are expected to invite other respondents to take part in the prevention or early detection of cervical cancer by performing a pap smear, reducing the number of cervical cancer sufferers and deaths caused by cervical cancer.